Firenze e la lingua italiana fra nazione ed Europa Atti del convegno di studi Firenze, 27-28 maggio 2004 - Maraschio, Nicoletta (Firenze University Press, 2007)
The volume collects the proceedings of the conference "Firenze e la lingua italiana tra nazione ed Europa" (Florence and the Italian language between nation and Europe), which was held from on May 27 and 28 2004 in the Aula Magna of the University of Florence and the Accademia della Crusca. As known, Florence played a central role in the process of national linguistic unification and thanks to its international vocation the city has promoted the spread and knowledge of the Italian language and culture all over Europe and in the world. Beyond any celebratory enthusiasm, the conference has been an occasion of open discussion on the cultural identity of the city in the contemporary context, through a critical reflection on its history (in particular on some significant moments of the Florentine culture between the nineteenth and twentieth centuries) and on its linguistic primacy.